Borrowinds associated with the names of clothing and jewelry (according to the linguistic corpus data) - Salikzhanova Ш.Б.; Tokenkyzy Г. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
The article analyzes the use and stylistic function of the names of clothing and jewelry in modern language. Texts containing names of clothing and jewelry, which served as the basis for the analysis, were taken from the database “Small Corpuses of the National Corpus of the Kazakh Language”. During the analysis of these texts, words associated with the names of clothing and jewelry in the modern Kazakh language are introduced, their modification, the adoption of additions characteristic of the Kazakh language, etc. A linguistic analysis of its features has been made. In addition, the article reflects lexicology, including the conclusions of famous scientists who have conducted research related to foreign words. During the analysis of the collected material, it was possible to draw a conclusion about the following frequency paradigm of lexemes. Names associated with women’s clothing and fashion, valuable information obtained by examining the names of jewelry from the point of view of historical etymology, allows us to determine the historical layers of names associated with women’s clothing and fashion, and obtain valuable information from the ancient history of the language. Today it has been established that words associated with clothing names are often used. It can be seen that names of clothes from English are also intensively used in our language. The fact that it is often used in the language of young people is reflected in the texts of the linguistic corpus. The lexical group is replenished not only by the emergence of new types of fashion models and items for face, hair care and clothing, but also by the spread in our country of things that have been in fashion in other countries for some time. It is necessary to promote the use of Kazakh equivalents of fashion-related names. From the language of the analyzed media texts, it was established that most of the names of women’s sportswear are words from other languages.